Linking Patient Safety Culture, Job Satisfaction, And Nursing Care Quality: Evidence From Private Hospitals - Asroriyah Zulia Khozanah; Irviana Fitriyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Patient safety and nursing care quality are two crucial aspects of healthcare delivery. Todays, ensuring a robust patient safety culture is fundamental to achieving high standards in nursing care. This present study aims to investigate the relationship between patient safety culture and nursing care quality. In addition, job satisfaction assessed as mediating variable. Using convenience sampling technique, a total of 236 nurse participated in the survey during February until April 2024. The respondents are nurses who works in private hospital, located in Tangerang. SPSS 26 is employed as a statistical tool to assess path analysis. The result showed that patient safety culture has a positive influence on nursing care quality. Patient safety culture also shares positive effect on nurse’s job satisfaction. In addition, based on the sable test result, job satisfaction significantly mediates the connection between patent safety culture and nursing care quality. These findings suggest that enhancing patient safety culture not only improves the quality of nursing care but also boosts nurses’ job satisfaction. Therefore, interventions aimed at strengthening patient safety culture can provide dual benefits in improving healthcare outcomes.